Study of the austempering transformation kinetics in compacted graphite cast irons - Gregorutti, Ricardo Walter (2004)
In this work, the phases involved in the transformation austenite→ferrite+high-carbon austenite in cast irons were assessed by means of Mossbauer spectroscopy and hardness measurements for samples austempered at five different temperatures between 573 and 673 K with two Mn contents. The C content in the high-carbon austenite was found to have a dependence of t0.40±0.05 on the austempering time t, which evidences that diffusion of carbon has taken place. The kinetic parameter k determined using the Johnson-Mehl-Avrami equation has a maximum of 3.9×10−3 (s−1) at ≈623 K and corroborates that Mn slows the transformation rate.